HUBUNGAN KEMAMPUAN KOMUNIKASI GURU DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS XI DI SMA N 1 IV KOTO - Putria Ningsih; Arifmiboy (JURNAL ILMIAH PENELITIAN MAHASISWA, 2023)
Abstract. This research is motivated by the fact that the learning outcomes of teacher and student communication skills are very important in learning. Because communication skills are important for students to achieve learning. This type of research is quantitative and correlational in nature. The population in this study was class XI students consisting of 5 classes. The sampling technique is Cluster Random Sampling, namely with a sample size of 30 students, instruments in the form of questionnaires and documentation. The research results show that there is a significant relationship between teacher communication skills and student learning outcomes as evidenced by the known r count of 0.737 while the r table is 0.3610. and the significance test a= 0.05. Meanwhile the person correlations value obtained was 0.761, meaning it shows a positive relationship that the better the teacher's communication, the higher the student learning outcomes. The correlation coefficient is 0.761. It can be concluded that the correlation value is strong because it is in the range 0.60-0.79. So, it is concluded that there is a relationship between teacher communication skills and student learning outcomes in class XI PAI subjects at SMA N 1 IV Koto.